Inverted Classroom: An Active Methodology in Learning - Martins, Olga Aparecida da Silva (2021)
The book addresses, in an engaging way, the active methodology that is currently highlighted due to the pandemic we are experiencing, but also leads us to a reflection and motivation to know, in more detail, and according to the two educators, motivated by a very simple question "What is the best solution for my students" what ideas have been evolving and reaching the current practice of today and disseminated, at the world level, exposing their successes and failures and revealing, also, the experiences gained, leading to the improvement of the method and the proper guidelines for those who want to be part of this universe. Which does not mean that it will be an easy task: teaching never is.